HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA TERHADAP PANDEMI COVID-19 DI SMK N 1 RENGAT KABUPATEN INDRAGIRI HULU - Putri, Monalisa Ananda; Wulandhari, Yopi; Bahriyah, Fitriyani (Universitas Batam, 2021)
Coronavirus Disease (COVID-19) is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV2) virus which can attack the respiratory system. The purpose of this study was to determine the relationship between knowledge and attitudes towards the Covid-19 pandemic at SMK N 1 Rengat in 2021. The method used is analytical method with Randome sampling technique. This research was obtained at SMK N 1 Rengat in 2021, amounting to 79 respondents. Data analysis used the chi-square test. The results showed that knowledge of adolescents was good as many as 56 people (71%) and adolescent attitudes were positive as many as 43 people (54%). The result of statistical analysis shows the p-value = 0.000. The conclusion of this research is that there is a significant relationship between the level of knowledge and attitudes of adolescents towards the Covid-19 pandemic at SMK N 1 Rengat in 2021.